THE EFFECT OF TEMPE FERMENTATION TIME ON THE TOTAL PHENOLIC AND ISOFLAVONE GENISTEIN CONTENTS - Suharto, Kiki Fransiska; Soetjipto, Hartati; Martono, Yohanes (ALCHEMY Jurnal Penelitian Kimia, 2017)
The objective of this study was to evaluate total phenolic compounds and isoflavone genistein contents during 0 - 9 days of fermentation time. Isoflavone extract were obtained by maceration and fractionation. Total phenolic compounds were measured by Folin ciocalteau method, meanwhile, the isoflavone genistein contents were analyzed by a High Performance Liquid Chromatography. The yield of isoflavone extract and the total phenolic compounds were analyzed using a randomized completely block design and the mean between treatments was compared by the Honestly Significant Difference (HSD) test using significance level of 5 %. The highest amount of total phenolic compounds during the incubation time was obtained on 4 days of fermentation time, i.e., 232.05n ± 7.71 μg/g, while the highest content of isoflavone genistein was obtained on 5 days of fermentation time, i.e., 100.48 μg/g. This research confirms that the fermentation process of tempe induces the total phenolic contents and the production of isoflavone genistein is fluctuating.